Pemikiran Hukum Islam Salafi-Wahabi dalam Pandangan Ulama Fikih Empat Mazhab - Paraga, Andi Wulanjiha Noer; Paraga, Sukardi; Madina, Dinda Difia; Majid, Nur Julian (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to find out more deeply about the emergence of Salafi and its legal thinking, analyze how the istinbath method was used and how the views according to the scholars of fiqh 4 madzhab Researchers use descriptive qualitative research methods is a type of research that aims to gain an in-depth understanding of a particular phenomenon or topic. This research uses a library research model with reference sources through journal articles and books that explain the research theme. The results of this study indicate that there are factors that caused Salafi Islamic law to be revived, one of which is Muhammad bin Abdul Wahhab thought that Muslims were misguided in religion and did not return to the Qur'an and As-Sunnah. Still, his thinking was wrong, and also this movement has very radical (hard) thoughts in religion and easily disbelieves someone when they have different thoughts from them. The method of istinbath carried out by Salafis is different from the scholars of the 4 madhhabs, salafis only focus on the Qur'an, sunnah, and the opinions of scholars from their circles, while the scholars of the 4 madhhabs have other istinbath besides the Qur'an and Hadith. The impact of the implementation of Salafi Islamic Law thinking is different from the legal thinking of the 4 madhhabs, namely salafis require a woman from their circle to cover the whole body including the face. In comparison, the scholars of the 4 madhhabs only require covering the whole body except the face and palms.